Green synthesis of TiO2 nanoparticles prepared from Phyllanthus niruri leaf extract for dye adsorption and their isotherm and kinetic studies - Anitha Panneerselvam; Jeevanantham Velayutham; Sudha Ramasamy (IET Nanobiotechnology)
Abstract Herein, the green synthesis of TiO2 nanoparticles using Phyllanthus niruri leaf extract was accomplished by the sol‐gel method. The structure and particle size of the synthesised TiO2 nanoparticles were characterised by X‐ray diffraction (XRD) analysis and the size was found to be 20 nm. The Fourier‐transform infrared spectra determined the existence of carboxyl and hydroxyl functional groups. The images from SEM analysis recommended a porous and heterogeneous surface. The methyl orange (MO) dye removal was examined using different parameters such as pH, time, dose, temperature and dye concentration. Maximum dye elimination percentage was achieved at pH 6.0 and 0.02 g as the optimum adsorbent dose. The kinetic analysis suggested that the pseudo‐second‐order kinetic model finely defines adsorption dynamics. Langmuir adsorption isotherm studies revealed endothermic monolayer adsorption of the methyl Orange dye. The negative value of ∆G° and positive value of ∆H° showed the spontaneous and endothermic adsorption method.